Training and Supervision as Predictors of Business Teachers’ Job Performance for Policy and Practice in Nigerian Secondary Schools - Tijani, Abdulganiyu Adebayo; Etejere, Patricia Agnes O. (International Business Education Journal, 2021)
This study investigates training and supervision as predictors of business teachers’ job performance in Nigerian public secondary schools. A survey research design is adopted for the study. The population consists of 1,500 business-related subject teachers from four states in Nigeria’s North Central Geo-Political Zone. 550 samples are purposely selected as the respondents from 20 schools. A structured questionnaire is used to collect relevant data from the respondents. Three experts from the Department of Business Education, Kwara State University, validated the questionnaire. The reliability coefficient of 0.71 was obtained through a split-half method. The hypotheses generated were tested using correlation and multiple regression analysis. The results show a strong correlation between training and teachers’ job performance (r = .786) but a very low correlation between supervision and teachers’ job performance (r = .089). Moreover, training and supervision explain the variation in teachers’ job performance by 52.0%. Training and supervision indicate a positive influence on teachers’ job performance. Regular capacity building such as workshops and conferences were recommended for the teachers in addition to the regular external and internal supervision. The government should also supply the necessary teaching facilities to help the teachers improve teaching and learning.